Unveiling the Unforeseen - Steve Henry; Emma Smith; Ginger Grant; Jan Hendrick Roodt; Lisa Anketell; Neils Bjerre Tange; Thomas Iskov (Journal of Innovation in Polytechnic Education)
A group of researchers have collaborated for three years to explore learner agency across vocational contexts in Canada, Denmark, and New Zealand. To investigate the learning from this collaboration, participants carried out a collaborative autoethnography. Participants wrote their perspectives and themes, which were distilled. What emerged is a community of practice that has generated unexpected trust and depth. The cultural exchange and diversity-building have changed previous views of each other’s practices. There has been significant personal and professional growth for all participants. The collaboration has led to an increased criticality, something all participants noted would not have been possible without the freedom to be candid about the challenges and changes they face in their home contexts. What began as an inquiry into learner agency has resulted in the researchers becoming the unexpected learners by unveiling unforeseen insights into their own practices.